Analisis Hasil Belajar Fisika Aspek Kognitif Pada Siswa Kelas XI IPA Pondok Pesantren Nurul Hakim - Subaidi, Subaidi; Qothrunnada, Qothrunnada (Indonesian Publication Center, 2023)
This quantitative descriptive study aims to analyze the cognitive learning profiles of 11th grade science students at MA Dakwah Islamiyh Pondok Pesantren Nurul Hakim based on Bloom's Taxonomy hierarchy (C1-C6). The research subjects consisted of 27 female students who were tested using an essay test instrument. The results showed that the students' average cognitive score was 89 with a 100% mastery level. However, in-depth analysis revealed a paradox in achievement; students were very dominant at the lower cognitive level (Lower Order Thinking Skills), particularly Remembering (C1) and Applying (C3), but experienced significant difficulties at the levels of Understanding (C2), Analyzing (C4), Evaluating (C5), and Creating (C6). This phenomenon is thought to be influenced by the double cognitive burden of the pesantren curriculum and a strong culture of memorization with minimal conceptual reflection. The study concludes that there is a need to transform the learning model from passive-receptive to active-constructive in order to improve the higher-order thinking skills of santri.